Asesmen Risiko PT Empat Pilar Anugerah Sejahtera Berbasis ISO 31000:2018 - Akbar, Rexy Chalid; Muktiaji, Haryo Ridhonoto; Prasetyo, Aries Heru (Research Center and Case Clearing House (RC-CCH) - Sekolah Tinggi Manajemen PPM, 2022)
The research in this thesis is motivated by the risks at PT Empat Pilar Anugerah Sejahtera (PT EPAS). This research aims to conduct a risk assessment along with a treatment plan based on ISO 31000:2018 so that PT EPAS can identify and handle the risks that will arise. This type of research is applied research. The study uses qualitative data obtained by interviewing related parties regarding the scope, context, categories, and risk assessment. Data is also obtained by reviewing several sources of news portals to support external context data. The study results conclude that there are seventy-seven risks faced by PT EPAS, where strategic risk has the largest presentation and legal risk with the smallest percentage of the total risk faced by PT EPAS. The study results also conclude that there are ten risks with the greatest magnitude of risk that need to be prioritized to be handled.